(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2024)
Solar energy has been one of the most promising energy sources since the 1990s. However, the efficiency of solar panels is reduced due to dust accumulation over modules, which blocks the incident light from the sun. The efficiency of a solar panel depends on various factors, such as the quality of the solar cells, the design of the panel, the temperature and intensity of the sunlight, and the presence of any shading or obstructions. High-efficiency solar panels can produce more electricity from the same amount of sunlight, resulting in higher energy production and cost savings over the system’s lifetime. The study used a semi-automatic cleaning mechanism, which is one of the recent developments made on automated cleaning systems of solar photovoltaic modules. Aims of this study is to improve the efficiency of solar panels by designing and implementing a semi-automatic dust-cleaning mechanism. This study found that the experimental model shows improved efficiency by about 7 percent. The study’s findings are consistent with previous research that emphasizes the importance of regular cleaning of solar panels to improve their efficiency and reliability. This research has important implications for improving the efficiency and reliability of solar energy systems. Solar panel owners can improve the profitability and sustainability of their system, leading to more widespread adoption of solar energy by optimizing the cleaning process and reducing maintenance costs.